ANALISIS BALANCED SCORECARD UNTUK MENDUKUNG PENGENDALIAN CYBER FRAUD DI BANK CIMB NIAGA TAHUN 2022-2024 - Umi Solehah; Siti Rodiah; Zul Azmi (Komunitas Manajemen Kompetitif, 2026)
This study aims to examine the importance of cyberfraud control as the use of digital services in the banking sector increases, potentially creating cybercrime risks. The focus of this study is the implementation of cyberfraud control at Bank CIMB Niaga using the Balanced Scorecard (BSC) approach, which encompasses financial, customer, internal business process, and learning and growth perspectives. The research method used is qualitative, utilizing secondary data sourced from annual reports and sustainability reports for the 2022–2024 period. The results show that cyberfraud control at Bank CIMB Niaga has gradually strengthened through increased investment in technological security, improvements to internal business processes, and increased organizational readiness for digital transformation. These findings demonstrate that effective cyberfraud control requires technological support, a robust risk management system, and an organizational commitment to maintaining sustainable information security